2011
DOI: 10.1210/en.2010-1456
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Regulates Embryonic Survival During Delayed Implantation

Abstract: Delayed implantation, considered a state of suspended animation, is widespread in mammals. Blastocysts under this condition remain dormant for an extended period but resume implantation competence upon favorable conditions. The underlying mechanism by which extended longevity of dormant blastocysts is maintained is not clearly understood. Using autophagy markers and the well-defined delayed implantation model in mice, we show that autophagy is important for the extended longevity of dormant blastocysts in uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 36 publications
6
96
0
1
Order By: Relevance
“…5A. This pattern is similar to the punctate pattern exhibited in blastocysts obtained from GFP-LC3 transgenic mice (Lee et al 2011). We also confirmed by western blotting that the internalized LDP12-EGFP-LC3 fusion proteins undergo PE conjugation and produce LC3-II forms.…”
Section: Ldp12-mediated Protein Transduction In Blastocystssupporting
confidence: 85%
“…5A. This pattern is similar to the punctate pattern exhibited in blastocysts obtained from GFP-LC3 transgenic mice (Lee et al 2011). We also confirmed by western blotting that the internalized LDP12-EGFP-LC3 fusion proteins undergo PE conjugation and produce LC3-II forms.…”
Section: Ldp12-mediated Protein Transduction In Blastocystssupporting
confidence: 85%
“…By immunofluorescence staining, LC3-II form appears as puncta in the cytoplasm, indicating their accumulation in autophagosomes and autophagolysosomes (Lee et al 2011). As shown in Fig.…”
Section: Resultsmentioning
confidence: 67%
“…We previously showed that mouse blastocysts show heightened autophagy when implantation is delayed by ovariectomy (OVX) on day 4 of pregnancy (Lee et al 2011). Under conditions of estrogen deprivation, dormant blastocysts survive in utero while the uterine quiescence is maintained by daily P 4 injection (Dey & Lim 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It was also hypothesized that autophagy in trophectoderm might be a surviving mechanism of dormant blastocysts in an experimentally delayed implantation model. 11 These findings imply that autophagy is involved in the placental pathophysiology in addition to apoptosis.…”
Section: Introductionmentioning
confidence: 95%